HBV and HCV testing outcomes among marginalized communities in Italy, 2019–2024: a prospective studyResearch in context - Monica Monti; Teresita Caruso; Alice Castellaccio; Irene De Giorgi; Gabriella Cavallini; Maria Laura Manca; Serena Lorini; Silvia Marri; Luisa Petraccia; Francesco Madia; Cristina Stasi; Laura Carraresi; et al. (The Lancet Regional Health. Europe)
Summary: Background: The health of the marginalized populations is crucial for public health and inequalities. The World Health Organization (WHO) Global Hepatitis Report 2024 stated that over 304 million people were living with Hepatitis B Virus (HBV)/Hepatitis C Virus (HCV) infection in 2022. We performed HBV/HCV screenings among marginalized communities to reveal hidden infections and link-to-care positive participants. Methods: From January 2019 to May 2024, finger-prick tests were used to conduct on-site screenings at non-profit organizations in Tuscany, Italy. Positive participants were referred to the closest outpatient clinic. Findings: Eighty/1812 (4.4%) participants were Hepatitis B surface Antigen (HBsAg)+, mostly men (p < 0.001) and non-Italian natives compared to those HBsAg- (p < 0.001). Fifty-two/1812 (2.9%) were anti-HCV+ with a higher proportion of Italians (p < 0.001) and lower education level (p < 0.01) compared to the anti-HCV-. Intravenous drug use was an independent factor for being anti-HCV+ (p < 0.0001). Among the HBsAg + individuals, 66.3% (53/80) were linked and 90.4% (48/53) retained in care (treated/monitored). Of the anti-HCV participants requiring clinical evaluation, 37.8% (14/37) were linked to care, and all the 11/14 (88.6%) viremic patients were successfully treated. Interpretation: We found higher HBV/HCV positivity compared to national prevalences. Participation and linkage to care were successful. The young mean age (33.6 yrs) of HBsAg + individuals, primarily from regions with low vaccinal adherence, indicated geographical origin as a key risk factor. HCV positivity was associated with extreme marginality. The results stress the need to implement marginalized groups screening to target HBV/HCV hidden infections, reducing disparities in healthcare and advancing towards the WHO 2030 elimination goal. Funding: Gilead Sciences; Fondazione Cassa di Risparmio di Pistoia e Pescia; Regione Toscana.